Less Favored – More Favored? Women’s Approaches to Property After Re-marriage During the Second Half of the 18th Century - Grochowina, Nicole (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
Due to the greater interest in the relationship between gender and history, as it has been emphasized after the “cultural turn” of the 1990s, questions concerning women’s roles in early modern legal practice became an important focus of research, too. First of all, criminal laws came into view: Questions were raised, why women were being hunted as witches, and whether they should be regarded as victims of the legal system. Furthermore, studies asked, how gender was constructed, when, for instance, fornication was being tried at court. Despite these efforts, research did not focus on civil legal practice with the same inten-sity. It appeared, that corresponding cases were regarded as less spectacular than issues of criminal law. Moreover, the existence of several judicial instruments like the guardianship seemed to have suggested that women could not be regarded as independently acting subjects of law. Instead, they were expelled from early modern legal culture. Nevertheless, it has to be argued, that such an impression is not sufficient enough to understand the relationship be-tween gender and law in the early modern society. In fact, it appears that women were not excluded from civil legal practice at all. Studies on marriage, marriage contracts and inheri-tance of women suggest a different picture.